The first part of the second line, she left the -5 there. The correct work and solution should be this:
5(2x-1)-3x=5x+9
<span><span>7x</span>−5</span>=<span><span>5x</span>+<span>9
</span></span>2x-5=9
2x=14
x=7
Answer:
D and C
Step-by-step explanation:
You just write the numbers and see how many zeroes they have
If you are trying to figure out the distance between the top of the tree and the end of the shadow, use a^2 + b^2 = c^2 where c is the hypotenuse and a and b are the legs of the right triangle.
5^2 + 4^2 = c^2
25 + 16 = c^2
41 = c^2
c = √41 = 6.4 meters
Answer:
-2/3
Step-by-step explanation:
Log125(1/25)=x
Raise each side to the base of 125
125^Log125(1/25)=125^x
1/25 = 125^x
Rewrite 25 as a power of 5 and 125 as a power of 5
1 / 5^2 = 5^3^x
The if power is in the denominator, we can bring it to the numerator by making it negative
5^-2 = 5^3^x
We know that a^b^c = a^(b*c)
5^-2 = 5^(3*x)
Since the bases are the same, the exponents are the same
-2 = 3x
Divide by 3
-2/3 = 3x/3
-2/3 =x